Thèmes en contexte - David NEUHAUS (Proche-Orient Chrétien, 2025)
In their statement of June 30, 2024, the members of the Justice and Peace Commission of the Assembly of Catholic Ordinaries in the Holy Land expressed their profound uneasiness with the use of the term “just war” within the context of the ongoing hostilities between Israelis and Palestinians in Gaza [...]